PENGARUH KOMPENSASI, KOMPETENSI, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN - Wawan Prahiawan; Dibyantoro Dibyantoro (Master of Management, Mataram University, 2023)
Employee performance makes a very important contribution to the sustainability of an organization facing increasingly competitive competition. For this reason, efforts are needed to improve employee performance in an organization. Compensation, competence, and organizational culture are some of the factors that were found to affect employee performance. The purpose of this study was to examine the effect of compensation, competence, and organizational culture on employee performance. The research method is quantitative using a questionnaire and the sampling technique is done by simple random sampling. The number of samples used as many as 34 pieces to test the three (3) hypotheses that have been set. Structural Equation Modeling (SEM) was used to test the statistical significance of the path coefficients. The analytical tool used is SmartPLS 3.2.9. The findings of the study explain that compensation has a positive and significant effect on employee performance. Competence has a positive and significant influence on employee performance. Organizational culture has a positive and significant influence on employee performance. The implications of the findings prove that the better the compensation, the higher the competence, and the better the organizational culture can improve employee performance.